Risk assessment of subcritical water hydrolysis (SWH) system for sugar recovery using failure modes and effects analysis (FMEA) methods - Nurfatimah Mohd Thani,; Siti Mazlina Mustapa Kamal,; Farah Saleena Taip,; Alifdalino Sulaiman,; Rozita Omar,; Mohd Hafizz Wondi, (Penerbit Universiti Kebangsaan Malaysia, 2022)
The subcritical water hydrolysis (SWH) process has proven to be an effective method for sugar recovery from bakery waste. However, the natural principle of the process involving high pressure and temperature has made it a hazardous operation. Hence, failure mode and effect analysis (FMEA) has been applied to identify the potential failure modes in subcritical water hydrolysis (SWH) systems. The Risk Priority Number (RPN) approach was used to rate each potential problem during the SWH process. The reactor unit was found to have the highest potential for failure by RPN value of 800 with the ‘failure effect analysis’ on the potential reactor cap to explode due to the very high pressure inside the reactor that developed during SWH. The failure consequences may lead to injury or even death. As a result of the FMEA assessment approach and several corrective action plans, the failure risks of SWH can be reduced and managed effectively.